Synthetic Derivatives against Wild-Type and Non-Wild-Type Sporothrix brasiliensis: In Vitro and In Silico Analyses - Lais Cavalcanti dos Santos Velasco de Souza; Lucas Martins Alcântara; Pãmella Antunes de Macêdo-Sales; Nathália Faria Reis; Débora Sena de Oliveira; Ricardo Luiz Dantas Machado; Reinaldo Barros Geraldo; André Luis Souza dos Santos; Vítor Francisco Ferreira; Daniel Tadeu Gomes Gonzaga; Fernando de Carvalho da Silva; Helena Carla Castro; et al. (MDPI AG, 2022)
Recently, the well-known geographically wide distribution of sporotrichosis in Brazil, combined with the difficulties of effective domestic feline treatment, has emphasized the pressing need for new therapeutic alternatives. This work considers a range of synthetic derivatives as potential antifungals against Sporothrix brasiliensis isolated from cats from the hyperendemic Brazilian region. Six S. brasiliensis isolates from the sporotrichotic lesions of itraconazole responsive or non-responsive domestic cats were studied. The minimum inhibitory concentrations (MICs) of three novel hydrazone derivatives and eleven novel quinone derivatives were determined using the broth microdilution method (M38-A2). In silico tests were also used to predict the pharmacological profile and toxicity parameters of these synthetic derivatives. MICs and MFCs ranged from 1 to >128 µg/mL. The ADMET computational analysis failed to detect toxicity while a good pharmacological predictive profile, with parameters similar to itraconazole, was obtained. Three hydrazone derivatives were particularly promising candidates as antifungal agents against itraconazole-resistant S. brasiliensis from the Brazilian hyperendemic region. Since sporotrichosis is a neglected zoonosis currently spreading in Latin America, particularly in Brazil, the present data can contribute to its future control by alternative antifungal drug design against S. brasiliensis, the most virulent and prevalent species of the hyperendemic context.